2023
DOI: 10.3389/fpsyt.2023.1210095
|View full text |Cite
|
Sign up to set email alerts
|

Service dogs for autistic children and family system functioning: a constant comparative analysis

Abstract: IntroductionService dog placements for autistic children are growing in popularity, yet findings to date are mixed. Moreover, no study to date has examined these placements through the lens of a recognized theoretical model. The purpose of this study is twofold: to explore experiences reported by caretakers of autistic children involved in a service dog program, and to contextualize findings within an established theoretical framework.MethodsA total of n = 50 caretakers of autistic children (n = 38 with and n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Taking into account the whole family system seems even more pertinent when one considers that having a pet in NT families can increase family adaptability and cohesion [ 108 ]. In a recent qualitative study of families of children with ASD with SDs, Leighton and collaborators [ 109 ] demonstrated that the presence of a SD contributes to strengthening and stabilizing the family unit, and improves the social functioning of the family unit (i.e., the interaction of the family with external systems such as other families, communities, schools, etc.). Thus, in order to further our understanding of the effects of SD integration on the family system, it would be of great interest to conduct studies that examine its effects from the family micro-system (i.e., family unit) to the family meso-system (i.e., peers, friends, school, community, etc.).…”
Section: Limits and Future Directionsmentioning
confidence: 99%
“…Taking into account the whole family system seems even more pertinent when one considers that having a pet in NT families can increase family adaptability and cohesion [ 108 ]. In a recent qualitative study of families of children with ASD with SDs, Leighton and collaborators [ 109 ] demonstrated that the presence of a SD contributes to strengthening and stabilizing the family unit, and improves the social functioning of the family unit (i.e., the interaction of the family with external systems such as other families, communities, schools, etc.). Thus, in order to further our understanding of the effects of SD integration on the family system, it would be of great interest to conduct studies that examine its effects from the family micro-system (i.e., family unit) to the family meso-system (i.e., peers, friends, school, community, etc.).…”
Section: Limits and Future Directionsmentioning
confidence: 99%
“…Currently, canines trained in ASD tasks are the third most requested service animals; however, many families cannot aff ord to purchase and properly care for a service canine for their child. 1 Animal-assisted therapy (AAT) can be a solution for those families. AAT requires strategic planning by the clinician to incorporate deliberate interventions into the child's care through direct and purposeful interaction with an animal in support of established therapy goals.…”
Section: Animal-assisted Therapy In Pediatric Autism Spectrum Disordermentioning
confidence: 99%